2018
DOI: 10.1637/11761-101917-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife Presence and Interactions with Chickens on Australian Commercial Chicken Farms Assessed by Camera Traps

Abstract: The types of wildlife and the frequency of their visits to commercial chicken farms in Australia were assessed using infrared and motion-sensing camera traps. Cameras were set up on 14 free-range layer farms, three cage layer farms, two barn layer farms, five non-free-range meat chicken farms, and six free-range meat chicken farms in the Sydney basin region and South East Queensland. Wildlife visits were found on every farm type and were most frequent on cage layer farms (73%), followed by free-range layer far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…No direct contact between live poultry and wild birds in the free‐range area was seen in our study, the same lack of interaction was observed in a recent field study with 20 free‐range poultry farms in Australia (Scott, Phalen, et al, ). It is hypothesized that AIV transmission to poultry on free‐range poultry farms will predominantly take place via indirect contact: taking up AIV by chickens via wild‐bird‐faeces‐contaminated water or soil in the free‐range area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No direct contact between live poultry and wild birds in the free‐range area was seen in our study, the same lack of interaction was observed in a recent field study with 20 free‐range poultry farms in Australia (Scott, Phalen, et al, ). It is hypothesized that AIV transmission to poultry on free‐range poultry farms will predominantly take place via indirect contact: taking up AIV by chickens via wild‐bird‐faeces‐contaminated water or soil in the free‐range area.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, this requirement is often neglected for practical and resource reasons. Scott, Phalen, et al (2018a) counted on average 2.4 wildlife visits per day per farm using motion-sensing camera traps (a total of 30 poultry farms in the study, camera traps operated for one week per farm in the period June-February), this is at least 10 times less than we have observed in our study. The order Passeriformes were the most frequent visitors to poultry farms in the Australian study (Scott, Phalen, et al, 2018a), with 1.6% of total wild bird visits identified by cameras by members of the orders Anseriformes and Charadriiformes.…”
Section: Known Carriers Of Ai Viruses Visit the Outdoor Facility Regumentioning
confidence: 70%
“…Therefore, a project that amasses 1 million images would require 10,000 hours for each image to be doubly observed. To reduce the number of images that need to be classified manually, ecologists using camera traps often limit the number of photos taken by reducing the size of camera arrays, reducing the duration of camera trap studies, and imposing limits on the number of photos a camera takes (Kelly et al, 2008; Scott et al, 2018). This constraint can be problematic in many studies, particularly those addressing rare or elusive species that are often the subject of ecological studies (O’Connell et al, 2011), as these species often require more effort to detect (Tobler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the Anatids, the species involved in AI ecology and epidemiology in poultry production areas in Australia remains largely unknown. Wild bird studies on Australian poultry farms have only occurred in recent years [16], and that particular study only used camera traps for a short period without the benefit of manual surveys to augment the interpretation of the data and bird behaviour.…”
Section: Australia Is a Relatively Isolated Island Continent And Not mentioning
confidence: 99%
“…Potential bridge species may include pest birds, rodents, and/or invertebrates [29,16]. Common Starlings (Sturnus vulgaris) and Rock Doves (Columba livia) are two potential avian bridge species for HPAI in North America.…”
Section: Other Bridge Speciesmentioning
confidence: 99%